The success rate of artificial insemination in Limousin crossbred heifer with additional concentrate - Putri Utami; Andriawan Soni Hantoro; Rizki Prafitri; Kuswati Kuswati; Asri Nurul Huda; Aulia Puspita Anugra Yekti; Trinil Susilawati (Universitas Sebelas Maret, 2024)
Objective: This study aimed to determine whether the addition of concentrate to heifers could be the same as the success of AI in calving cows in terms of Return Rate (NRR), Conception Rate (CR), and Pregnancy Rate (PR).Methods: The material used in this study was 28 Limousine Crossbred cows with 13 cows and 15 heifers. There were two treatments, namely T0: Cows that had given birth with control feed (control without added concentrate) + BIO ATP after AI, while T1: Heifers with control feed and the addition of 1kg/day concentrate for seven days after AI + BIO ATP. Samples were selected by purposive sampling with the criteria of BCS 3-5 (1-9) and aged ≥ 2 years. The artificial insemination method uses rectovaginal with 4+ deposition at the 2nd and 8th hour after estrus, then injection of Bio ATP brand